Current management of hepatocellular carcinoma: an Eastern perspective - Yim, Hyung Joon; Suh, Sang Jun; Um, Soon Ho (World journal of gastroenterology : WJG, 2015)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer death, especially in Eastern areas. With advancements in diagnosis and treatment modalities for HCC, the survival and prognosis of HCC patients are improving. However, treatment patterns are not uniform between areas despite efforts to promote a common protocol. Although many hepatologists in Asian countries may adopt the principles of the Barcelona Clinic Liver Cancer staging system, they are also independently making an effort to expand the indications of each treatment and to combine therapies for better outcomes. Several expanded criteria for liver transplantation in HCC have been developed in Asian countries. Living donor liver transplantation is much more commonly performed in these countries than deceased donor liver transplantation, and it may be preceded by other treatments such as the down-staging of tumors. Local ablation therapies are often combined with transarterial chemoembolization (TACE) and the outcome is comparable to that of surgical resection. The indications of TACE are expanding, and there are new types of transarterial therapies. Although data on drug-eluting beads, TACE, and radioembolization in Asian countries are still relatively sparse compared with Western countries, these methods are gradually gaining popularity because of better tolerability and the possibility of improved response rates. Hepatic arterial infusion chemotherapy and radiotherapy are not included in Western guidelines, but are currently being used actively in several Asian countries. For more advanced HCCs, appropriate combinations of TACE, radiotherapy, and sorafenib can be considered, and emerging data indicate improved outcomes of combination therapies compared with single therapies. To include these paradigm shifts into newer treatment guidelines, more studies may be needed, but they are certainly in progress.